Detection of peri-implant bone defects using cone-beam computed tomography and digital periapical radiography with parallel and oblique projection - Vadiati Saberi, Bardia (Imaging Sci Dent, 2019)
PURPOSE: To compare the diagnostic accuracy of cone-beam computed tomography (CBCT) with that of parallel (PPA) and oblique projected periapical (OPA) radiography for the detection of different types of peri-implant bone defects. MATERIALS AND METHODS: Forty implants inserted into bovine rib blocks were used. Thirty had standardized bone defects (10 each of angular, fenestration, and dehiscence defects), and 10 were defect-free controls. CBCT, PPA, and OPA images of the samples were acquired. The images were evaluated twice by each of 2 blinded observers regarding the presence or absence and the type of the defects. The area under the receiver operating characteristic curve (AUC), sensitivity, and specificity were determined for each radiographic technique. The 3 modalities were compared using the Fisher exact and chi-square tests, with P<0.05 considered as statistical significance. RESULTS: High inter-examiner reliability was observed for the 3 techniques. Angular defects were detected with high sensitivity and specificity by all 3 modalities. CBCT and OPA showed similar AUC and sensitivity in the detection of fenestration defects. In the identification of dehiscence defects, CBCT showed the highest sensitivity, followed by OPA and PPA, respectively. CBCT and OPA had a significantly greater ability than PPA to detect fenestration and dehiscence defects (P<0.05). CONCLUSION: The application of OPA radiography in addition to routine PPA imaging as a radiographic follow-up method for dental implantation greatly enhances the visualization of fenestration and dehiscence defects. CBCT properly depicted all defect types studied, but it involves a relatively high dose of radiation and cost.